Effects of a Macro-Nutrient Preload on Type 2 Diabetic Patients - Li, Chun-Jun; Norstedt, Gunnar; Hu, Zhao-Gian; Yu, Pei; Li, Dai-Qing; Li, Jing; Yu, Qian; Sederholm, Magnus; Yu, De-Min (Frontiers in Endocrinology, 2015)
Aims: Macro-nutrient preloads given 30 minutes before regular meals may improve metabolism. The aim was to investigate how type 2 diabetic patients react to a preload consisting of a blend of macro-nutrients with a low glycemic index (Inzone Preload ®). Methods: In a before-after study design, 30 subjects with type 2 diabetes mellitus (T2DM) were enrolled in a 12-week program. All subjects were given Inzone Preload (43 % proteins, 29% carbohydrates, 10 % lipids and 9 % fibers,71 kcal), 30 min before each meal during 12 weeks. Fasting glucose, postprandial 2h glucose were monitored every second week. Body weight (BW) and waist circumference were measured each month. Fasting plasma glucose, glycosylated hemoglobin, serum lipids, fasting insulin, C-reactive protein and homeostasis model assessment were evaluated before and after the intervention. Subjective appetite was monitored using visual analogue scales after the Inzone Preload. Results: The dietary intervention significantly influenced several metabolic parameters compared to base line. Inzone Preload treatment reduced mean postprandial plasma glucose levels (12.2 ± 1.2 mmol/L vs 10.5 ± 2.0 mmol/L), HbA1c (7.4 ± 0.3 % vs 7.1 ± 0.2 %), mean total cholesterol (4.8 ± 0.9 mmol/L vs 4.3 ± 0.8 mmol/L), low-density lipoprotein cholesterol (2.8 ± 0.6 mmol/L vs 2.5 ± 0.4 mmol/L) and CRP (1.5 ± 1.4 mg/L vs 0.7 ± 0.7 mg/L) BW loss of more than 3% was seen in 13 participants (43%). Feelings of satiety were significantly higher after Inzone Preload than after habitual breakfast (p < 0.05). No significant changes in fasting blood glucose, high-density lipoprotein and total triacylglycerol, HOMA-IR, and HOMA-β were observed. Conclusions: A macro-nutrient preload treatment reduces postprandial glucose, inflammatory markers and serum lipids in patients with T2DM. Approximately half of the study group also displayed reduced body weight.